Add-on Pegylated Interferon Alpha-2a Therapy in Chronic Hepatitis B Japanese Patients Treated with Entecavir. (11th April 2017) - Tamai, Hideyuki; Ida, Yoshiyuki; Shingaki, Naoki; Shimizu, Ryo; Fukatsu, Kazuhiro; Itonaga, Masahiro; Yoshida, Takeichi; Maeda, Yoshimasa; Moribata, Kosaku; Maekita, Takao; Iguchi, Mikitaka; Kato, Jun; et al.
Abstract : Entecavir requires long-term administration. Pegylated interferon (PEG-IFN) therapy leads to significant reduction of hepatitis B surface antigen (HBs Ag) levels. This study aimed to assess the safety and efficacy of adding PEG-IFN- α -2a to entecavir toward cessation of entecavir. A total of 23 patients treated with entecavir underwent add-on PEG-IFN- α -2a therapy (90  μ g per week) for 48 weeks. Viral response (VR) was defined as more than 50% reduction of baseline hepatitis B surface antigen (HBs Ag) level at 72 weeks from the start of therapy. Complete response (CR) was defined as the decline of HBs Ag levels <100 IU/mL. Hepatitis B e antigen (HBe Ag) seroconversion rate was 25% (2/8), and VR rate was 52% (12/23). CR was observed in four patients (17%). However, CR rate in baseline HBs Ag level <2000 IU/mL and HBe Ag negative patients was 50% (4/8). Univariate analysis showed that the percentage of HBs Ag level reduction at week 12 was significantly associated with VR. The area under the curve value was 0.848. Adding PEG-IFN- α -2a to entecavir has limited efficacy. The percentage reduction of HBs Ag level at week 12 may be a useful predictor for VR.